(3OhQ GdfTGW GdLeGYj dMUI GdJQHjI GdHOfjI h GdQjGVjI aj JYRjR bje GdehGWfI (B: (3ebGQHI GLJeGYjI JQHhjI dKGfhjGJ GdebGWYI GdZQHjI dhdGjI GdTda s - (3MGL Hf YjThT , SGde s; (3ZVHGf, GMeO MeRIs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2023)
(3ef NdGd GdOQGSI GdJj befG aj HMKfG gPG fCed Edi eYQaI OhQ GdfTGW GdQjGVj GdLeGYj aj MUI GdJQHjI GdHOfjI h GdQjGVjI aj JYRjR bje GdehGWfI GdWhQ GdKGfhj, hef NdGd GWdGYfG Ydi eHGOF hbje GdCfTWI GdQjGVjI GdLeGYjI GdehLhOI aj efgGL ef CHYGO CNdGbjI h GLJeGYjI, h GbJUGOjI befG HEfTGA GSJHjGf ehLg Edi GdJdGejP jJchf ef KdGK eMGhQ eMhQ NGU HGdCHYGO GdCNdGbjI dJfejI GdehGWfI, h eMhQ GdKGfj NGU HGdCHYGO GdGLJeGYjI dJQbjI bje GdehGWfI eMhQ KGdK NGU HGdCHYGO GdGbJUGOjI eSJYedjf GdefgL GdhUaj GdJMdjdj Ydi YjfI ef GdJdGejP ddWhQ GdKGfhj debGWYI GdZQHjI dhdGjI Tda GdeJchfI ef (B1455 (3JdejP MjK GNJjQJ GdYjfI HTcd YThGFj MjK CLGH GdJdGejP Ydi (B60 (3SDGd ddeMGhQ GdKdGK ddGSJHjGf hJe MSGH ELGHGJge dYOO GdJcQGQGJ HGdfSH GdeFhjI h GNJHGQ cG(B2 (3hef NdGd GdeYWjGJ h GdfJGFL GdeJMUd YdjgG aj YedjI JaQjZ GdGSJHjGf JHjf dfG Cf GdaQVjGJ ddOQGSI bO JMbbJG HTcd ehLH HGdJGdj GSJfJLfG Cf eYXe GdJdGejP jYJHQhf Cf GdfTGW GdLeGYj dMUI GdJQHjI GdHOfjI h GdQjGVjI jfej bje GdehGWfI GdUGdMI(B.s
(3OcJhQGIs
Keywords: (3GdehGWfI s; (3GdfTGW GdHOfj GdJQHhj GdeOQSjs; (3OQS GdJQHjI GdHOfjI h GdQjGVjIs